5x+6=3x+9

Simple and best practice solution for 5x+6=3x+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+6=3x+9 equation:


Simplifying
5x + 6 = 3x + 9

Reorder the terms:
6 + 5x = 3x + 9

Reorder the terms:
6 + 5x = 9 + 3x

Solving
6 + 5x = 9 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
6 + 5x + -3x = 9 + 3x + -3x

Combine like terms: 5x + -3x = 2x
6 + 2x = 9 + 3x + -3x

Combine like terms: 3x + -3x = 0
6 + 2x = 9 + 0
6 + 2x = 9

Add '-6' to each side of the equation.
6 + -6 + 2x = 9 + -6

Combine like terms: 6 + -6 = 0
0 + 2x = 9 + -6
2x = 9 + -6

Combine like terms: 9 + -6 = 3
2x = 3

Divide each side by '2'.
x = 1.5

Simplifying
x = 1.5

See similar equations:

| 28-4x=7-7x | | 10x-16=9x+2 | | 5(x+4)=3x+29 | | 4(x+2)-2=18 | | y-3.5=-21 | | -5j+78=8j-2 | | 3x-19=5x+2 | | 5-(2u-1)=14-4u | | x*2-2x=0 | | 3x-19=x-2 | | 2.23-3.14x=2x-4.195 | | 2(4x+3)=2 | | 4x-15=x+10 | | 5x-12=2x-9 | | 2H+4S=22 | | 5(x-3)=-13 | | 19-x+4+x+19+x-1=34 | | 3x=1.08 | | F(x)=(radx-2)-3 | | ln(3-7x)=-2 | | 3x+1.66=1.8 | | 10x^3+58x^2+43x-11=0 | | 10x^3+58x^2+43x-11=f(x) | | 24x=-16x^2+6 | | 5x-7y=29 | | 5cos(x)=0 | | 0.04*0.8= | | x+(2x+15)=150 | | 0.75d-0.67d=0.67+6 | | 88+5x= | | K-(-6)=-33 | | x+0.5x+0.25x+1=100 |

Equations solver categories